Methods to reduce soil erosion and nutrient losses in Kavre district, central Nepal - Paper withdrawn - Pathak, Janak (Himalayan Journal of Sciences, 2006)
Withdrawal notice of a research paper published in Vol 2, issue 3 Dear readers, Upon the request of author, we are retracting a paper entitled “Methods to reduce soil erosion and nutrient losses in Kavre district, central Nepal” published in the volume 2, issue 3 of Himalayan Journal of Sciences under the category “research paper.” The author writes: “The research was primarily a part of my Bachelor’s dissertation work at Kathmandu University. It also contained a part of the work to which I worked as an associate. After publication, as it turned out, there are some fundamental flaws in the reporting of the result, and that makes the discussion and conclusion invalid. With a deep regret, I would like to withdraw my published article and request you to announce this notice to the scientific community as soon as possible. I am very sorry for the misreporting, wasting time and effort of editors and reviewers, and for the misinformation to the readers.” Such errors are bound to occur in any field, and this prompt retraction is a reflection of the scientist's integrity. We look forward to being able to post the author's revisions. ? Editor Himalayan Journal of Sciences 2(3): 42-45, 2004